Milliwatt power UV-A LEDs developed by using n-AlGaN superlattice buffer layers grown on AlN templates - Matsumoto, Takuma; Ajmal Khan, M; Maeda, Noritoshi; Fujikawa, Sachie; Kamata, Norihiko; Hirayama, Hideki (Journal of physics. D, Applied physics, 2019)
Ultraviolet (UV)-A light-emitting diode (LED) light sources are strongly demanded for both medical and photochemical applications. In our previous report, we investigated the conventional n-AlGaN buffer layer (BL)-based UV-A LED devices and a very low output power was achieved. In this work, we aim for the suppression of vertically propagating threading dislocation densities (TDDs) in the n-AlGaN BL including the current spreading layer (CSL) by introducing Si-doped n-Al0.37Ga0.63N/n-Al0.27Ga0.73N superlattices (SLs) between the AlN template and n-AlGaN BL for the demonstration of 341 nm UV-A LEDs. When the conventional n-AlGaN BLs were replaced with n-AlGaN SL-based BLs (with a suitable number of periods up to ~70) in the UV-A multi-quantum wells, then the full width at half maximum of the x-ray rocking curves in the n-AlGaN CSL for the (0 0 0 2) and (10-12) planes, respectively, were reduced to 346 and 431 arcsec and the total TDDs were suppressed to approximately ~1  ×  109 cm−2. Finally, when the conventional Ni (20 nm)/Au (150 nm) p-electrodes were replaced with new Ni (1 nm)/Mg (200 nm) p-electrodes in the n-AlGaN SL-based UV-A LEDs, the maximum output power was improved from 2.1 to 2.5 mW.